The Influence of Independence and Interest on Online Biology Learning Outcomes at South OKU District Senior High School - Novitasari, Novitasari; Hidayat, Saleh; Seri, Herman (UIN Fatmawati Sukarno Bengkulu, 2021)
Independence is the ability of students to manifest their desires and desires in a real way withoutdepending on others. In addition to independent learning, interest also has an influence on studentlearning outcomes. The Minister of Education and Culture has issued Circular Number 4 of 2020 that thelearning process is carried out at home through online learning during the Covid-19 outbreak, onlinelearning is carried out according to the abilities of each school. The research objectives were to determine:1) the effect of independent learning on the results of online biology learning at SMAN OKU SelatanDistrict?; 2) the influence of learning interest on the results of online biology learning at SMAN SouthOKU Regency 3) the influence of independence and interest in learning together on the results of onlinebiology learning at SMAN South OKU Regency?. Research Method: Descriptive Quantitative. Researchresults: there is a significant effect of independent learning on learning outcomes of biology with asignificant value of 0,002 <0,05 with a contribution value of 47% while 53% is influenced by othervariables not examined, namely children's readiness and intelligence, on interest there is a significantinfluence on the results. learning biology with a significant value of 0,023 <0,05 with a contribution valueof 45% while 55% is influenced by other variables that are not examined, namely habits and a willingnessto learn as well as independence and interest in learning together, there is a significant effect on thelearning outcomes of biology with a value significant amounting to 0,001 <0,05 with a contribution valueof 52%, while 48% is influenced by other variables not examined, namely teacher competence andlearning methods. Conclusion: There is a significant effect of independence and interest in learning on thelearning outcomes of biology at Public Senior High School in South OKU District.